Representación comunicacionales de las fiesta de la niña María de Jerusalén en San Miguelito de Píllaro - Asadobay Ayala, Jonathan Estuardo (2020)
This research addressed the problem related to the lack of communication strategies regarding the dissemination of activities carried out by the festivities of the Girl Mary of Jerusalem in the parish of San Miguelito de Píllaro, with the aim of creating communication proposals in social networks. For this, a qualitative approach methodology was used, combining the bibliographic and field design, using the techniques of interviewing a historian, the pastor and the board of directors of the priostes of the holiday, as well as the discussion group with residents of the San Miguelito parish. Which has allowed us to obtain as a result that this celebration has deeprooted religious and cultural significance in the population. However, in recent years the influx of visitors has been decreasing in the development of the festivities, due to multiple factors, among which is the lack of a powerful communicative strategy, which is known and disseminates the symbolism and representativeness of this Celebration at local, national and international level. Therefore, it is considered necessary to develop communications products as an informative guide, advertising campaigns, video documentaries and live broadcasts of the various activities that are part of this celebration in the San Miguelito parish..